“The hidden Filter”: Quantifying the ecological role of Lithophaga lithophaga (Linnaeus, 1758) in Mediterranean benthic-pelagic processes - T. Marrocco; A. Petrucciani; B. Calcinai; S. Puce; C. Cerrano; A. Norici (Marine Environmental Research, 2026)

An integrative study of Anemonia viridis (Forsskål, 1775) and Aiptasia couchii (Cocks, 1851) (Cnidaria: Anthozoa) from the North Adriatic Sea - S. Arossa; C. Cerrano; M. Barucca; F. Carducci; S. Puce; C. G. Di Camillo (Zoomorphology, 2021)

White matter abnormalities of microstructure and physiological noise in schizophrenia - Hu Cheng; Sharlene D. Newman; Jerillyn S. Kent; Amanda Bolbecker; Mallory J. Klaunig; Brian F. O’Donnell; Aina Puce; William P. Hetrick (Brain Imaging and Behavior, 2015)

Zanclea–coral association: new records from Maldives - S. Montano; D. Maggioni; P. Galli; D. Seveso; S. Puce (Coral Reefs, 2013)

Genus Distichopora (Cnidaria, Hydrozoa): from primary cyclosystem to adult pore organisation - S. Puce; D. Pica; F. Brun; L. Mancini; G. Bavestrello (Coral Reefs, 2012)

Population dynamics of Eudendrium racemosum (Cnidaria, Hydrozoa) from the North Adriatic Sea - C. G. Di Camillo; F. Betti; M. Bo; M. Martinelli; S. Puce; C. Vasapollo; G. Bavestrello (Marine Biology, 2012)

Lytocarpia and Cladocarpus (Cnidaria: Hydrozoa, Aglaopheniidae) from the Bunaken National Marine Park (North Sulawesi, Indonesia) - C. G. Di Camillo; S. Puce; G. Bavestrello (Marine Biodiversity, 2011)

First evidence of a specific association between a stylasterid coral (Cnidaria: Hydrozoa: Stylasteridae) and a boring cyanobacterium - S. Puce; S. Tazioli; G. Bavestrello (Coral Reefs, 2009)

Hydrozoa (Cnidaria) symbiotic with Porifera: a review - S. Puce; B. Calcinai; G. Bavestrello; C. Cerrano; C. Gravili; F. Boero (Marine Ecology, 2005)
Many hydroids are symbiotic with other organisms. Sponges, because of their complex canal system and their filter‐feeding activity inducing a continuous water flow, are used by numerous species as either exclusive or facultative substrata. The associated hydroid fauna thriving on or inside sponges shows a wide range of relationships with their hosts. Hydroids may be simply epibiotic on sponges, their stolons running on the host surface. Alternatively, the stolons may grow inside the sponge body, the polyps emerging from the sponge surface, having also the possibility of retraction inside the sponge tissue. Finally, stolons and branches may develop deeply inside the sponge body, producing a skeletal network for sponge growth. This paper reviews the described relationships of hydrozoans symbiotic with sponges and reports new observations.

Organism–quartz interactions in structuring benthic communities: towards a marine bio‐mineralogy? - C. Cerrano; A. Arillo; G. Bavestrello; U. Benatti; B. Calcinai; R. Cattaneo‐Vietti; L. Cortesogno; L. Gaggero; M. Giovine; S. Puce; M. Sarà (Ecology Letters, 1999)
Abiotic and biotic factors determine the distribution and structure of marine benthic communities but the processes invoked to explain such patterns are often inadequate. We demonstrate that the presence of quartz grains in sediments inhibits animal colonization on marine soft‐bottoms. We suggest that this phenomenon may be related to the oxidant properties of the quartz crystal surface derived by the generation of silicon‐based radicals due to water movement. The interaction between organisms and the crystallographic structure of substrata might play a neglected but important role in structuring coastal benthic communities.